Gamma-secretase-dependent signaling of receptor tyrosine kinases - Merilahti JAM; Elenius K (My University, 2022)
Human genome harbors 55 receptor tyrosine kinases (RTK). At least half of the RTKs have been reported to be cleaved by gamma-secretase-mediated regulated intramembrane proteolysis. The two-step process involves releasing the RTK ectodomain to the extracellular space by proteolytic cleavage called shedding, followed by cleavage in the RTK transmembrane domain by the gamma-secretase complex resulting in release of a soluble RTK intracellular domain. This intracellular domain, including the tyrosine kinase domain, can in turn translocate to various cellular compartments, such as the nucleus or proteasome. The soluble intracellular domain may interact with transcriptional regulators and other proteins to induce specific effects on cell survival, proliferation, and differentiation, establishing an additional signaling mode for the cleavable RTKs. On the other hand, the same process can facilitate RTK turnover and proteasomal degradation. In this review we focus on the regulation of RTK shedding and gamma-secretase cleavage, as well as signaling promoted by the soluble RTK ICDs. In addition, therapeutic implications of increased knowledge on RTK cleavage on cancer drug development are discussed.